Institutional Challenges in Implementing DAPODIK as a Basis for Education Decision-Making in Indonesia - Munawar Fajri; Hizir Sofyan; Niswanto Niswanto; Amri Amri; Sabariah Sabariah (Journal of General Education and Humanities, 2025)
The Data Pokok Pendidikan (DAPODIK) system serves as the primary foundation for educational data management and policy decision-making in Indonesia. However, persistent institutional challenges continue to affect the accuracy and reliability of the data. This research aims to identify and analyze the institutional obstacles that hinder the effective implementation of DAPODIK. Using a descriptive qualitative method, the study explores three key dimensions: infrastructure, institutional structure, and human resources. The findings reveal that (1) inadequate internet connectivity and unstable electricity disrupt data entry and synchronization; (2) weak policy integration, limited budgets, and inconsistent leadership commitment impede effective data governance; and (3) insufficient training for school operators reduces technical competence, thereby compromising data validity. These findings highlight the need for a comprehensive reform strategy that strengthens digital infrastructure, enhances institutional governance, and develops human resource capacity to ensure reliable education data management.